HUBUNGAN ANTARA KREATIVITAS GURU DENGAN PRESTASI BELAJAR SISWA DI SDN PEMURUS DALAM 5 BANJARMASIN - Fadliah, Rina (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
This study aims to investigate the relationship between teacher creativity and student academic achievement at SDN Pemurus Dalam 5 Banjarmasin. Employing a quantitative approach, the research involved 20 students from class VB as the sample, drawn from a total population of 400 students. Data were collected through questionnaires and documentation, and analyzed using the Pearson product-moment correlation method. The results indicate that the level of teacher creativity falls within the moderate category, with an average score of 52.7. Despite this, teacher creativity was found to have a significant positive contribution to students’ learning outcomes. The statistical analysis revealed a correlation coefficient of r = 0.796, which exceeds the critical values of r_table = 0.444 at the 5% significance level and r_table = 0.561 at the 1% significance level. Therefore, the alternative hypothesis (Hₐ), stating that there is a relationship between teacher creativity and student academic achievement, is accepted. This study presents a novel contribution by empirically demonstrating a strong correlation between teacher creativity and student achievement at the elementary level a domain that has received limited attention in correlation-based quantitative research, especially in public schools. The findings emphasize the critical role of creative pedagogical practices in enhancing student learning performance, particularly in lower grade classrooms where instructional dynamics often rely heavily on teacher initiative. .